Design of A Web-Based Social Network Information System - Tata Sutabri (International Journal of Artificial Intelligence Research, 2022)
In this modern era, the community's need for information is growing, especially the need for the internet, which can provide information more quickly and according to requirements. The internet is one of the developments in information technology that allows time and distance to be no longer a limit for obtaining information. Social networking sites are web-based services that enable users to create profiles, view a list of available users, and invite or accept friends to join the site. The basic appearance of this social networking site displays the user's profile page, which consists of the user's identity and photo. The emergence of this social networking site was initiated by an initiative to connect people from all parts of the world. Facebook is a social networking service and website launched in February 2004 that is operated and owned by Facebook had more than 500 million active users. 50% of active users log in 2 to Facebook every day, and the average user has one hundred and fifty friends. Users can create personal profiles, add other users as friends, and exchange messages, including automatic notifications when they update their profiles. By utilizing internet facilities, communication in sharing information can be done quickly and easily. For this reason, using internet facilities can create a web-based application that can offer fast and easy communication. This application system is made by designing input, output, database, and user interface. The design results are then implemented into PHP, CSS, JavaScript, and MySQL scripts used for database management. So that a web-based application is produced that can facilitate communication.